2011
DOI: 10.1371/journal.pmed.1000407
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Preventive Treatment of Malaria Provides Substantial Protection against Malaria in Children Already Protected by an Insecticide-Treated Bednet in Mali: A Randomised, Double-Blind, Placebo-Controlled Trial

Abstract: A randomized trial reported by Alassane Dicko and colleagues shows that intermittent preventive treatment for malaria in children who are protected from mosquitoes by insecticide-treated bednets provides substantial protection from malaria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
128
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(160 citation statements)
references
References 28 publications
(44 reference statements)
17
128
2
1
Order By: Relevance
“…By contrast, the post-intervention prevalence of quadruple mutants in Mali was significantly higher in the SP + amodiaquine-IPTc group than the placebo group, and prevalence also increased from baseline in the IPTc group but not in the placebo group 70 . In Senegal, post-intervention prevalence of triple Pfdhfr and Pfdhps A437G mutants was also significantly higher in the SP + artesunate treatment arm than the placebo arm, despite an increase in both groups from baseline 69 .…”
Section: Children and Smc/iptcmentioning
confidence: 68%
“…By contrast, the post-intervention prevalence of quadruple mutants in Mali was significantly higher in the SP + amodiaquine-IPTc group than the placebo group, and prevalence also increased from baseline in the IPTc group but not in the placebo group 70 . In Senegal, post-intervention prevalence of triple Pfdhfr and Pfdhps A437G mutants was also significantly higher in the SP + artesunate treatment arm than the placebo arm, despite an increase in both groups from baseline 69 .…”
Section: Children and Smc/iptcmentioning
confidence: 68%
“…The inoculation dose dependency seen in this study definitely seems to suggest so. Perhaps a more practical application of our findings for a P. berghei clone that had been selected for highlevel pyrimethamine resistance in the blood stage but that remained partially susceptible to pyrimethamine during liverstage development is to help explain the somewhat surprising protective efficacy of IPT with SP in infants and children despite a high prevalence of antifolate resistance (4,14). These findings also indicate that an adjustment of the currently inappropriate SP dose (5) may entail a disproportional increase in the chemoprophylactic efficacy after each IPT dose.…”
Section: Vol 55 2011mentioning
confidence: 96%
“…First, only a single, though very visible, study demonstrated sustained protection during 1 year of follow-up in children who had received IPT in their first year of life (35). Subsequent studies were unable to replicate this intriguing finding and, in some instances, even suggested a rebound effect (4,14). Second, it is controversial whether homologous challenge in the P. berghei-C57BL/6 model reflects the effect of protective immune responses in human infections with P. falciparum.…”
Section: Vol 55 2011mentioning
confidence: 99%
“…Of the two trials, which considered severe anemia as a separate outcome, both also found a significant reduction as a result of IPT (Dicko et al, 2011; Konate et al, 2011). This is consistent with the findings of a previous Cochrane review, which had also concluded that IPT in pregnant women was similarly associated with decreased rates of both severe anemia and all anemia (Garner and Gulmezoglu, 2006).…”
Section: Malaria Prevention Efforts Reduce Anemia Prevalencementioning
confidence: 98%